การปรับปรุงประสิทธิภาพการใช้พลังงานของเตาเผามูลฝอยติดเชื้อโดยการนำแก๊สปล่อยทิ้งมาอุ่นอากาศเผาไหม้ - ภาวัต ประทุมศิริ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This thesis presents improvement of a biomedical incinerator efficiency by preheating combustion air with exhaust gases. Biomedical incineration is one of high energy consuming processes due the high moisture content of biomedical waste. In order to ensure that no hazardous gases in exhaust gases, it is required by law that there are at least two combustion chambers the second of which must be maintained at temperature not lower than 1000℃. Therefore, the exhaust gases temperature is very high and waste heat is correspondingly high. This study targets at recovering the waste heat for combustion air preheating. This not only reduces waste heat loss but also improves incinerator efficiency. The results based on air preheater designed and installed on the biomedical incinerator at Pathumthani Hospital indicate that energy consumption is reduced by 23%. Gas emissions from the stack before and after installation of air preheater are within that required by the regulation. Carbon monoxide drops from 440 ppm to 53 ppm. Moreover, incomplete combustion from the stack is significantly reduced.